2020
DOI: 10.1155/2020/5240153
|View full text |Cite
|
Sign up to set email alerts
|

Association of Urine Albumin/Creatinine Ratio below 30 mg/g and Left Ventricular Hypertrophy in Patients with Type 2 Diabetes

Abstract: Several studies show that even a level of urine albumin/creatinine ratio (UACR) within the normal range (below 30 mg/g) increases the risk of cardiovascular diseases. We speculate that mildly increased UACR is related to left ventricular hypertrophy (LVH) in patients with type 2 diabetes mellitus (T2DM). In this retrospective study, 317 patients with diabetes with normal UACR, of whom 62 had LVH, were included. The associations between UACR and laboratory indicators, as well as LVH, were examined using multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(36 reference statements)
1
5
0
1
Order By: Relevance
“…Our observations add to more and more evidence, and they challenge the idea that UACR< 30 mg/g means albumin excretion is “normal” [ 27 ]. Our research is more focused on “normal” urine albumin excretion, so we divide the urine protein-creatinine ratio into three groups, divide the range of proteinuria with a limit of 30 mg/g, and then divide the “normal” urinary albumin to creatinine ratio by 10 mg/g is divided into two groups.…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…Our observations add to more and more evidence, and they challenge the idea that UACR< 30 mg/g means albumin excretion is “normal” [ 27 ]. Our research is more focused on “normal” urine albumin excretion, so we divide the urine protein-creatinine ratio into three groups, divide the range of proteinuria with a limit of 30 mg/g, and then divide the “normal” urinary albumin to creatinine ratio by 10 mg/g is divided into two groups.…”
Section: Methodssupporting
confidence: 52%
“…In 2020, another Chinese study showed that urinary albumin-creatinine ratio (UACR) within the normal range (less than 30 mg/g) would also increase the risk of cardiovascular disease. The optimal cut-off value of UACR for diagnosing diabetic left ventricular hypertrophy is 10 mg/g [ 27 ]. In our study to predict all-cause death, we used the same cut-off value, and the results were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, A cohort study with an up to11-year follow-up period found that protein excretion levels, even with normal at baseline, are pronouncedly associated with increased mortality risk from CVD ( 17 ). A recent study also confirmed that a normal ACR range (≤30 mg/g) was related to left ventricular hypertrophy in patients with T2DM ( 18 ). This suggested that the specific numerical changes of ACR and the risk thresholds might not be fully reflected when we simply treated ACR as a categorical variable with a 30 mg/g cut-off.…”
Section: Introductionmentioning
confidence: 62%
“…22,24 Xie et al studied and found association between UACR and left ventricular hypertrophy in Type 2 diabetes patients. 26 Lo et al studied and found beneficial effects of SGLT-2 inhibitor Empagliflozin on cardiovascular and Renal outcomes in Diabetic patients. 25 Our study compared Diabetic patients with and without Hypertension for UACR and eGFR.…”
Section: Discussionmentioning
confidence: 99%